Optimasi Penggunaan Lahan Tanaman Pangan dalam Ketahanan Pangan di Kecamatan Tenjo, Kabupaten Bogor: Optimizing Land Use for Food Crops in Food Security in Tenjo District, Bogor Regency - Yunus Arifien Arifien; Sari Anggarawati Anggarawati; Ratna Sari Hasibuan (Universitas Nusa Bangsa, 2025)
ABSTRACT This study aims to evaluate and optimize agricultural land use in Tenjo District, Bogor Regency, to increase the availability and economic value of local food commodities. Using a linear optimization model, the study utilized land area data and the rupiah conversion value per hectare for key food commodities such as lowland rice, upland rice, corn, cassava, and sweet potato. The optimization model used an objective function approach to maximize the total rupiah value, with fixed land area and technical constraints. Simulation results show that transferring a small portion of land from low-value commodities to commodities with high economic value can increase total income by approximately: Rp 98–99 billion per year, depending on the optimization approach. An increase of approximately 3% from the current condition. billion per year, depending on the scenario and market prices used. These results confirm that targeted land allocation based on the economic potential of each commodity can increase land use efficiency without having to expand agricultural areas, which is in line with the concept of sustainable agriculture and regional food security. The recommended cropping pattern needs to be implemented through proportional empowerment of farmer groups according to the area of land and labor owned. Information networks on land and human resources must be built and developed so that available resources can be utilized optimally to support comprehensive agricultural development at the regional level. Keywords: food security, optimization, and land use